Innovations and innovative in domestic banking: Theoretical aspect - Natalia Mostovenko (Економічний форум)
The publication is dedicated to substantiating the thesis that the modern development of banking is impossible using only traditional approaches in creating effective banking business models. The sphere of financial entrepreneurship is significantly different from the sphere of material production or provision of various types of services. Until recently, innovative activity was identified with the technical and technological development of enterprises, scientific and technological progress, and production processes. However, the effect of the introduction of innovations and the growth of the role of the service sector led to the fact that innovations became the driver of the formation of new consumer properties not only of goods, but also of services. Thus, routine approaches and traditionalism no longer meet the needs of the financial services market, customer requests. Given the significant differences between financial intermediation and other types of business, the implementation of innovations and implementation of innovative activities in banking is different from those innovative processes that accompany the sphere of material production. Therefore, questions of methodology and practice of using innovations and innovative activities in banking as a form of financial intermediation do not lose their relevance. In order to reveal the theoretical content of the concepts, the presented article examines the existing author's approaches to the definition of the concept of «banking innovations», analyzes their common features and highlights essential differences. It is substantiated that the dependence of banks on the development and introduction of innovations in the business model is manifested in two planes. First of all, banking competition is intensifying, and the strengthening of a specific bank's own competitive position is impossible without new ideas and innovations. The most obvious in this regard is the development of the so-called «product» line of the bank. However, only changing the product line will not be a guarantee of market success. Separately, it is worth emphasizing the fact that in order to build a successful banking business model, it is necessary to implement innovative approaches to the set of measures that form the content of the bank's management system. Secondly, the question of ensuring and maintaining a certain financial stability in the banking system in general and individual banks in particular, which takes on a special meaning during the introduction of martial law and military operations, is now acute. The key to financial stability can be new tools in the anti-crisis management system, which are impossible without the general innovative focus of the banking business